The effect of 8 weeks core combined lower limb strength training on adolescent swimmers' medley turning technique - Sun, K., Pan, D., Qi, Y., & Xu, F. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
This study aimed to explore the effects of core combined lower limb strength training on medley turning technique of adolescent swimmers. Ten adolescent swimmers completed the trunk extensor and flexor endurance tests, squat jump test and 200m individual medley race before and after the 8 weeks training. The time of extensor and flexor endurance, jump height, and the maximal acceleration in swimming turns had significantly increased after training. The -5 m to 5 m times, the tuck times, and the hip and knee joint angles had significantly decreased after training. Eight weeks core combined lower limb strength training can improve the core strength and lower limb power, optimize the tuck technique, reduce the -5 m to 5 m time and increase the maximum acceleration during the swimming turns in 200m individual medley.